Ethnomathematics: Mathematical Concepts In The Gaple Card Game - Afandi, Muhammad Irfan; Almaghfiroh, Violina; Marhayati (Jurnal Fourier, 2024)
The purpose of this research is to describe the mathematical elements contained in the gaple card game. This study uses ethnographic research with a qualitative approach. The focus of this research is the tools, rules and processes of the gaple card game. Data collection techniques used are observation, interviews, field notes, and documentation. This study uses triangulation data analysis which consists of data reduction, presentation and conclusion. The results of this study found mathematical concepts in the gaple card game, namely set, addition, opportunity and inequality.